2008
DOI: 10.1161/atvbaha.108.177113
|View full text |Cite|
|
Sign up to set email alerts
|

Hypercholesterolemia Enhances 15-Lipoxygenase–Mediated Vasorelaxation and Acetylcholine-Induced Hypotension

Abstract: Objective-Arachidonic acid (AA) metabolites from 15-lipoxygenase-1 (15-LO-1), trihydroxyeicosatrienoic acid (THETA), and hydroxyepoxyeicosatrienoic acid (HEETA) relax arteries. We studied 15-LO-1 expression, THETA and HEETA synthesis, and their effect on arterial relaxations and blood pressure in hypercholesterolemic nonatherosclerotic rabbits. Methods and Results-Immunoblots, RTPCR analysis, and 14 C-AA metabolism revealed that hypercholesterolemia increased 15-LO-1 expression in the endothelium and THETA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In normotensive rats and cholesterol-fed, normotensive rabbits, inhibition of LOs with phenidone, baicalein, or BW755c did not affect basal blood pressure or heart rate (2,149). Similarly, the basal blood pressure was identical in wild-type and 12/ 15-LO knockout mice (5).…”
Section: Role Of Lo Metabolites In Regulating Vascular Tone In Vivomentioning
confidence: 85%
See 1 more Smart Citation
“…In normotensive rats and cholesterol-fed, normotensive rabbits, inhibition of LOs with phenidone, baicalein, or BW755c did not affect basal blood pressure or heart rate (2,149). Similarly, the basal blood pressure was identical in wild-type and 12/ 15-LO knockout mice (5).…”
Section: Role Of Lo Metabolites In Regulating Vascular Tone In Vivomentioning
confidence: 85%
“…In normal rabbits, ACh decreased blood pressure in a concentration-related manner (1)(2)(3). Treatment with inhibitors of COX and NOS reduced, but did not block, the ACh-induced hypotension (1).…”
Section: Role Of Lo Metabolites In Regulating Vascular Tone In Vivomentioning
confidence: 99%
“…Although the source of these metabolites has not been identified at this stage of research [219] later expression silencing studies [220] and adenovirus mediated somatic gene transfer [221, 222] suggested the involvement of ALOX15 . Interestingly, chronic hypoxia and hypercholesterolemia enhanced ALOX15 mediated vasorelaxation in rabbit arteries [223, 224]. More direct evidence for the in vivo relevance of ALOX15 in blood pressure regulation was recently provided by experiments with ALOX15-deficient mice [225].…”
Section: Biological Function Of Mammalian Lox Isoformsmentioning
confidence: 99%
“…Because the majority of atherogenic risk factors are associated with increased 12/15-LO expression (5)(6)(7)(8), and disruption of 12/15-LO gene-protected ApoE Ϫ/Ϫ mice from developing high-fat diet-induced atherosclerosis (24), we studied the role of 12/15-LO in EC barrier dysfunction. A quiescent monolayer of HUVECs, when treated with 5-, 12-, and 15(S)-HETE, the AA cleavage products of 5-, 12-, and 15-LO, the paracellular permeability of the monolayer, as measured by passive diffusion of FITC-conjugated dextran, significantly increased (Fig.…”
Section: (S)-hete Increases Ec Permeability-loss Of Barrier Func-mentioning
confidence: 99%